If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3(y+1)=19-15y
We move all terms to the left:
3(y+1)-(19-15y)=0
We add all the numbers together, and all the variables
3(y+1)-(-15y+19)=0
We multiply parentheses
3y-(-15y+19)+3=0
We get rid of parentheses
3y+15y-19+3=0
We add all the numbers together, and all the variables
18y-16=0
We move all terms containing y to the left, all other terms to the right
18y=16
y=16/18
y=8/9
| 6d+8=14+33d | | 9+5x=7x-11 | | 2x+12+2x+5=7x+1 | | 5-3(2-x)=4x-7 | | )9=-3/8r | | -28r=4r | | 3a-7=2(6a+5) | | -3(x+8)=33 | | -2(-2)c=8 | | 6(x-12)=2(11x-4) | | –15w−–16w−–15=11 | | x+7x+1=180 | | -(x-7)=11 | | 3x+7-5x=-13 | | y/3y=48 | | 1-3x=1-x | | (2b-6)/6=2/3 | | 5x-3(x-4)=-6+5-6 | | 8.52-11.8b=-18.4b-8.91 | | 7x–2=x–14 | | 2(4x−3)=4x−30 | | 8z-3(2z-4)=3(z-6) | | 3(5x-5)+2=7x+11 | | 8(2w-3)-w=3(3w+2) | | 13+5x-2x=3 | | 1-2x+24x=2x+7x+49 | | 3x+4(x-17)=12 | | -3-10z=-17-16-8z | | 9x+4=-6+2x+24 | | 6n=–8+5n | | 5x-22=-2x-7 | | -4(3p+5)+8p=-11 |